the QUALITY OF ECOPRINT LEATHER PRODUCED USING THE BOILING TECHNIQUE - pancapalaga, wehandaka; Mahmud, Ali; Umar, Malikah (Universitas Djuanda, 2025)
The aim of this study is to determine the quality of ecoprint leather under different boiling temperatures and durations. The research method used was an experimental approach with a Completely Randomized Design (CRD) in a factorial pattern with two factors, First factor: Boiling temperature (60˚C, 70˚C, 80˚C) Second factor: Boiling duration (1.5 hours and 2 hours).The measured variables included leather quality parameters such as tensile strength, seam strength, tear strength, leather elongation, and color fastness to wet and dry rubbing. The results showed that the interaction between boiling temperature and duration had a significant effect (P>0.01) on ecoprint leather quality, particularly in terms of tensile strength, seam strength, tear strength, and color fastness to both dry and wet rubbing. Conclusion The quality of ecoprint leather is influenced by boiling temperature and duration in the ecoprinting process. It is recommended that the ecoprinting process on tanned leather be conducted at a boiling temperature of 70˚C for 2 hours